Media Grafis dalam Pembelajaran dan Implikasinya terhadap Motivasi Belajar Siswa - Rafif Taufiqul Hakim; Muhammad Amran; Muhammad Ridha (ASSUNNAH PRESS, 2026)
Abstract This study aims to explore the impact of the use of graphic media in learning on enhancing students’ learning motivation. Specifically, the study examines: (1) the influence of graphic media on students’ learning motivation, (2) factors affecting the successful implementation of graphic media in the learning process, and (3) the effectiveness of graphic media for both teachers and students in instructional activities. This study employs a qualitative approach using a literature review method. Data were obtained through the examination of various relevant written sources, including scholarly journals, books, and articles that discuss the use of graphic media in education and its effects on students’ learning motivation. The analysis was conducted to identify patterns, concepts, theories, and findings from previous studies related to the topic under investigation. The results indicate that the use of graphic media has significant potential to enhance students’ learning motivation by presenting information in a more engaging, visual, and easily comprehensible manner. Furthermore, the effectiveness of graphic media is influenced by several factors, including the alignment of the media with instructional content, teachers’ competence in utilizing the media, and students’ characteristics. These findings suggest that graphic media can be optimally employed as an instructional strategy to improve students’ learning motivation.